Tourism Marketing Strategies and Cultural Approach of BUMDes Murakabi Using TOWS Analysis - Guntur Andi; Sutopo; Tri Hartanto; Teresa Freitas Belo; Ashok Aima (International Journal of Economic and Tourism Research, 2026)
This research looks into BUMDes Murakabi's tourist marketing techniques in Kebondalem Kidul, with a focus on the importance of cultural integration in tourism growth. The study takes a qualitative approach, relying on interviews and document analysis to identify the strengths, weaknesses, opportunities, and threats (TOWS) influencing tourist marketing. The data show that BUMDes Murakabi employs a combination of digital and conventional marketing methods, such as social media promotions, influencer partnerships, and local cultural events. Despite these attempts, problems such as inadequate digital marketing knowledge, budget limits, and infrastructural limitations impede tourist growth. The report uses a TOWS analysis to make strategic suggestions. Key assets include a rich cultural past and active community engagement, but drawbacks such as limited promotional reach and dependency on seasonal tourists pose challenges. The increased interest in cultural and sustainable tourism creates opportunities, but problems such as competition and shifting visitor tastes represent considerable hazards. The strategy proposals focus on utilizing cultural heritage, improving digital marketing skills, procuring finance, and enhancing crisis management frameworks. This study adds to the theoretical framework of sustainable tourism marketing and offers practical insights to policymakers and tourism stakeholders. The findings emphasize the significance of balancing commercialization with cultural authenticity in order to achieve long-term viability. Future research should investigate the long-term impact of these initiatives on community resilience and economic growth. BUMDes Murakabi can strengthen its tourist competitiveness by combining cultural preservation with creative marketing strategies.